Peran Radio StArt FM Sebagai Media Komunikasi Dakwah Di Kabupaten Mandailing Natal - Datuk Imam Marzuki; Winda Meliana Hasibuan; Leli Arnita Hasibuan; Putri Romadonia; Ihsan Marzuki Nasution; Muhammad Tabroni Nasution; Ilham Syaputra Nasution (BADAN PENERBIT STIEPARI PRESS, 2024)
StArt FM radio is a medium for da'wah communication that can be heard by hundreds of people, even thousands of people. The role of StArt FM radio is to really help the public to get information such as current news, preaching studies, entertainment, random chats, promoting tourist attractions and introducing Mandailing cultures. to the outside community.. With the existence of StArt FM radio which always brings the most up-to-date and up-to-date information, every listener doesn't miss out on information.Da'wah is a communication practice that takes various forms, ranging from personal communication, mass communication and group communication. In the digital era, da'wah is faced with the challenge of conveying the message of Islam through mass media. The use of radio as a medium for da'wah communication is to use Islamic teachings as messages that must be conveyed by radio according to its function. The solution offered to maximize radio as a medium for da'wah communication is to create Islamic programs on radio, such as the OASIS program, Mutiara Qolbu, Islamic Reflection, Permata Hati and so on.In this case, it is certainly interesting to examine the role of StArt FM radio as a medium for da'wah communication in Mandailing Natal Regency. The research method used is qualitative-descriptive which seeks to describe the role of StArt FM radio as a medium for da'wah communication in Mandailing Natal Regency which has been going on so far. Meanwhile, the data collection technique uses interviews, observation and documentation as primary and secondary data sources. This research produces a picture that radio plays a role as a medium for conveying da'wah as a whole. With various OASIS programs, Mutiara Qolbu, Islamic Devotionals, Permata Hati and so on.